INSENTIF BAGI PENANAMAN MODAL ASING SEBAGAI UPAYA UNTUK MENCAPAI TUJUAN PEMBANGUNAN NASIONAL INDONESIA - Retno Hendrati Purwaningrum (Perspektif, 2002)
As we know, the purpose of National Development Program is to achieve a social justice and prosperous country based on Pancasila. So, it is understandable if Indonesian government invites and attracts foreign investors to do their business in Indonesia through many kinds of incentive, fiscal and non fiscal. However, the non fiscal incentive regulated in PP No. 20/1994 does not seem to work in accordance with the aims of National Development Program itself.